The Motivation Manual - Hagemann, Gisela; Gower Publishing Co. (Aldershot, Hampshire : Gower Pub. Co., 1992)
Applies motivational theory in management settings, offering exercises and case examples to help managers foster shared vision, trust, employee involvement in decision making, and improved productivity.
(3z(BPrize-winning(3y (Bedition description (as given in listing)s
Includes bibliographical references and index.
Keywords: Motivation (Psychology).; Employee motivation; Management; Business ethics (if relevant).